The 10q25 Neocentromere and its Inactive Progenitor Have Identical Primary Nucleotide Sequence: Further Evidence for Epigenetic Modification - Barry, Alyssa E.; Bateman, Melissa; Howman, Emily V.; Cancilla, Michael R.; Tainton, Kellie M.; Irvine, Danielle V.; Saffery, Richard; Choo, K.H. Andy

(untitled) (Genome Research, 2000)
We have previously localized the core centromere protein-binding domain of a 10q25.2-derived neocentromere to an 80-kb genomic region. Detailed analysis has indicated that the 80-kb neocentromere (NC) DNA has a similar overall organization to the corresponding region on a normal chromosome 10 (HC) DNA, derived from a genetically unrelated CEPH individual. Here we report sequencing of the HC DNA and its comparison to the NC sequence. Single-base differences were observed at a maximum rate of 4.6 per kb; however, no deletions, insertions, or other structural rearrangements were detected. To investigate whether the observed changes, or subsets of these, might be de novo mutations involved in neocentromerization (i.e., in committing a region of a chromosome to neocentromere formation), the progenitor DNA (PnC) from which the NC DNA descended, was cloned and sequenced. Direct comparison of the PnC and NC sequences revealed 100% identity, suggesting that the differences between NC and HC DNA are single nucleotide polymorphisms (SNPs) and that formation of the 10q25.2 NC did not involve a change in DNA sequence in the core centromere protein-binding NC region. This is the first study in which a cloned NC DNA has been compared directly with its inactive progenitor DNA at the primary sequence level. The results form the basis for future sequence comparison outside the core protein-binding domain, and provide direct support for the involvement of an epigenetic mechanism in neocentromerization.[The sequences in this paper have been submitted to GenBank under accession nos. AF222855 (not yet available) for HC; AF042484 for NCI; AF222854 (not yet available) for NCII; andAF222856 (not yet available) for PnC.]